Naskah Chujjatu Ash-Shiddîq Li Daf’i Az-Zindîq Karya Nuruddin Ar-Raniri (Kajian Filologi): Chujjatu Ash-Shiddîq Li Daf'i Az-Zindîq Written By Nuruddin Ar-Raniri (Philological Study) - Ferawati (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2022)
This research aims to analyze the physical and content of the Chujjatu As-Siddiq Li Daf`I Zindiq manuscript. The method used is the critical edition, namely editing the script by correcting some errors and irregularities, while the spelling is adjusted according to applicable regulations. There were word groupings, sentence divisions, and capital letters used as well as comments were also given regarding the text errors. Proper corrections are made based on perfect understanding as a result of comparisons between similar, and contemporary manuscripts. The manuscript written by Nuruddin Ar-Raniri has two versions, namely, script A and script B. The complete contents are 27 pages and talk about "fi bahts al-wujud wa nisba al-a`lam bi al-chaq ta`ala”. This manuscript was dated 1186 H. The language used is Arabic-Malay. The condition of the manuscript is still in good condition, the paper is brown and has small holes, the writing is legible, and the binding is intact. This manuscript discusses the teachings of Sufism and the stages of a person in acquiant his god.